Oscillating wave energy power generator for lift net fishing boat - Luther Sule; Parabelem Tinno Dolf Rompas (Institute of Advanced Engineering and Science, 2019)
This paper compares several designs of an oscillating wave power generator suitable for local net fishing boat in the waters of Tonyaman in the Strait of Makassar, Indonesia. The designs were based on wave height data for the period of January to December 2016 and of the local fishing vessel construction data. Several generator designs were created to replace diesel engines used by the local fishermen to power their boats’ lamps in the night. Results showed that DESIGN 5 with Arm length to buoy (L1) of 4 m and Arm length to pulley (L2) of 3 m and DESIGN 6 with L1 of 4 m and L2 of 2 m were the two designs most fitting for that purpose. Both designs could produce sufficient power ( ) to power the boats’ lamps in the shortest wave height condition (0.75 m) and the tallest wave height condition (1.5 m). At the shortest wave height condition (0.75 m), DESIGN 5 produced 14,237.58 W and DESIGN 6 produced 14,290.31 W. At the tallest wave height condition (1.5 m), DESIGN 5 and DESIGN 6 generated 28,285.31 W and 28,496.25 W of power, respectively.